The effect of repeated blood donations on the iron status of male Saudi blood donors - Abdullah, Saleh M. (Edizioni SIMTI — SIMTI Servizi Srl, 2011)
BACKGROUND. Regular blood donation can lead to iron deficiency. Screening donors’ serum ferritin levels at the time of first donation and subsequently once every year is a very rational way to pick up iron deficiency in a voluntary blood donor population. The aim of this study was to determine the effect of blood donation and the prevalence of erythropoiesis with iron deficiency (sideropenia) in Saudi male blood donors. MATERIALS AND METHODS. The study was prospectively conducted, between December 2008 and March 2009, on 182 male native Saudi blood donors at King Fahd Central Hospital in Jazan region, Saudi Arabia. Each donor gave 450±50 mL of whole blood. Following the donation, samples were removed into 2.5 mL EDTA tubes for measurement of mean cell volume (MCV) and mean corpuscular haemoglobin (MCH) and into 7.5 mL plain tubes for estimation of iron and serum ferritin concentrations. The blood donors were divided into five groups, according to the number of donations they had given in the preceding 3 years. The blood donors in group I were first-time donors, with no previous history of blood donation. Group II donors had donated once in the last 3 years. Subjects in groups III, IV and V had donated more than once in the preceding 3 years and were considered regular donors. RESULTS. The mean serum iron was significantly higher among subjects with no previous history of blood donation (group I) than among regular donors who had donated twice or more. The difference in serum ferritin concentration was statistically significant (p<0.05) when comparing regular donors in group III (72.4 μg/L), group IV (67.4 μg/L) and group V (26.2 μg/L) with first-time blood donors (131.4 μg/L). In contrast, the difference in the concentration of serum ferritin between subjects in group II (98.9 μg/L), who had donated once in the last 3 years, and in first-time blood donors (131.4 μg/L) was not statistically significant (p<0.131). None of the group I donors suffered from iron deficiency, whereas 2.8% of the donors who had donated between two to five times had iron deficiency. The prevalence of erythropoiesis with iron deficiency in regular blood donors was 4.3%. CONCLUSION. The results of this study show that an increase in the number of donations results in an increase in the frequency of depleted iron stores and subsequently in erythropoiesis with iron deficiency, although the level of haemoglobin remained acceptable for blood donation. This result may indicate the need to review the guidelines on acceptance of donors.